2017
DOI: 10.1515/pjct-2017-0048
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel production from vegetable oil: Process design, evaluation and optimization

Abstract: To investigate the effect of reactor performance/confi guration of biodiesel production on process parameters (mass & energy consumption, required facilities etc.), two diverse production processes (from vegetable oil) were implemented/designed using Aspen HYSYS V7.2. Two series reactors were taken into account where overall conversion was set to be 97.7% and 70% in fi rst and second processes respectively. Comparative analysis showed that an increase in conversion yield caused to consumption reduction of oil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…A variety of vegetable oils extracted from corn, canola, palm, soybean, sunflower, rapeseed, coconut, and groundnut have been converted into biodiesel [14][15][16]. However, as most of these plant-derived oils are initially used for food, livestock feed, and oleochemical industries, biodiesel production results in increased consumption of these resources and increased crop demand [10].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of vegetable oils extracted from corn, canola, palm, soybean, sunflower, rapeseed, coconut, and groundnut have been converted into biodiesel [14][15][16]. However, as most of these plant-derived oils are initially used for food, livestock feed, and oleochemical industries, biodiesel production results in increased consumption of these resources and increased crop demand [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical programming has been widely applied to optimize biodiesel process synthesis problem, considering the economic trade-offs and interactions among subsystems. By far the most systematically considered synthesis problems in biodiesel production is the heat exchanger networks synthesis, separation sequences, and superstructure optimization for alternative technologies [ 41 , 86 , 87 ]. This methodology was implemented by Martin et al [ 42 ] to perform superstructure optimization of biodiesel manufacturing from microalgae and waste vegetable oil.…”
Section: Optimizationmentioning
confidence: 99%
“…Nevertheless, the extraction, separation, and purification technologies have not been able to keep pace with the rapidly growing and ever eager market. , For example, Rosenthal (2014) reported that only 40–70% of potential CBD is successfully obtained as a product, and the rest is lost during different steps of its refinement . The reasons behind the poor progress in the field are twofold: first, the limits imposed by legal impediments, and second, the lack of thermodynamic data as a critical barrier against modeling studies and equipment design and development. , Among different separation technologies, vacuum evaporation and distillation offer several benefits, making it the proper choice for processing thermolabile blends. It takes advantage of vapor pressure and enables the boiling of different constituents at decreased temperatures.…”
Section: Introductionmentioning
confidence: 99%